Applicability and management of a scholar projects focused on the english subjects as a teaching strategy to 10th grade students at Daniel Octavio Crespo High School - Beitia, Lineth; Yuli Muñoz; De Gracia, Edwar; Vargas, Víctor; Mora, Christian; Tejeira, Roy (David, Panamá : UDELAS, 2013)
The implementation of scholar projects work has benefited studens from eduactional institutions in our country and all over the world. Due to the fact that such projects integrate theory and practice through the implementation of teaching strategies that effectively connect the knowledge obtained in the classroom real situations. Once our primary role is to organize and develop educational projects.
INDEX LIST OF TABLES LIST OF GRAPHICS INTRODUCTION CHAPTER I: BACKGROUND INFORMATION CHAPTER II: THEORETICAL FRAMEWORK 2.1. Stages of the scholar project development 2.2. Required techniques for the development of scholar projects in english subject 2.2.1. Collaborative learning 2.2.2. The case study 2.2.3. Problem solving technique 2.2.4. Brainstorming 2.3. Advantages develop in students using scholar projects 2.4. Evaluation models according to the process and execution of scholar projects strategy CHAPTER III: RESEARCH AND METHODOLOGY CHAPTER IV: DATA ANALYSIS AND INTEPRETATIONS OF RESULTS
Incluye Index
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
Np se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DELICENCIATURA; ENGLISH -- TESIS DE LICENCIATURA -- STRATEGY; FACULTAD DE EDUCACIÓN SOCIAL Y ESPECIAL; ESCUELA DE EDUCACIÓN SOCIAL; LICENCIATURA EN DOCENCIA EN INGLES; DANIEL OCTAVIO CRESPO - CHIRIQUÍ